Association of Employment Status With Symptom Burden and Health-Related Quality of Life in People Living With Primary CNS Tumors. (18th April 2023) - Leeper, Heather E.; Vera, Elizabeth; Christ, Alexa; Acquaye, Alvina; Briceno, Nicole; Choi, Anna; Grajkowska, Ewa; Jammula, Varna; Levine, Jason; Lindsley, Matthew; Reyes, Jennifer; Roche, Kayla N.; et al.
Abstract : Background and Objectives: Financial toxicity significantly affects many patients, especially cancer survivors. We evaluated the association of unemployment as a major contributor to financial toxicity with patient-reported outcomes (PROs) assessing multiple illness experience domains in a primary CNS tumor (PCNST) cohort. Methods: Patient and disease characteristics and PROs measuring symptom burden, interference, psychologic distress, functional impairment, and health-related quality of life (HRQOL) from participants enrolled in an institutional review board–approved observational study at the US NIH's Neuro-Oncology Branch were collected between September 2016 and December 2019. Descriptive statistics, tests of association, and comparison of group mean values were used to describe and evaluate PROs. Results: Of the 277 participants diagnosed with a PCNST, 57% were male and 43% were female. Participants reported their race as White, non-Hispanic (78%); White, Hispanic/Latino (9%); Asian (7%); Black (4%); Native Hawaiian/Pacific Islander (1%); and other (2%) with 8% missing. The median age of the overall cohort was 45 years (range 18–74). Hispanic participants in the overall sample were 2.3 times more likely, and in the brain tumor group 3.2 times more likely, to report unemployment ( p = 0.043, odds ratio [OR] 2.3, 95% CI 1.0–5.4 and p = 0.008, OR 3.2, 95% CI 1.3–7.9, respectively). 77 (28%) individuals unemployed due to tumor reported more functional impairment with walking, washing, dressing, and performing usual activities and reduced HRQOL ( p < 0.001). More unemployed participants in the total sample reported moderate-to-severe depressive symptoms (25%) than those employed (8%) (χ 2 (1) = 13.9, p < 0.001, OR 3.7, 95% CI 1.8–7.8) and more moderate-to-severe anxiety symptoms (30%) than those employed (15%) (χ 2 (1) = 7.8, p = 0.005, OR 2.4, 95% CI 1.3–4.5). Unemployed participants with brain tumor reported on average 3 more symptoms as moderate-to-severe compared with those employed ( t (83) = −4.0, 95% CI difference −5 to −2, p < 0.001, Hedge g = 0.70). Discussion: Being unemployed due to a PCNST strongly correlated with high symptom burden, functional impairment, psychological distress, and reduced HRQOL, which may be impediments to returning to work that warrant intervention. Lack of employer-based health insurance and reduced earnings are financial sequelae of unemployment superimposed on the physical, social, and cognitive effects of living with a PCNST. Innovations to screen for and address financial toxicity and its contributing factors are needed.